1974
DOI: 10.1104/pp.54.3.312
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Enzymology of the Glyceraldehyde 3-Phosphate Dehydrogenases from Pisum sativum

Abstract: Glyceraldehyde 3-phosphate dehydrogenases (EC 1.2.1.12 and 1.2.1.13) have been purified from the seed, root, etiolated, and green shoot of peas (Pisum sativum). These enzymes are tetramers of 140,000 daltons, with subunits of 35,000 daltons. The enzymes differ in isoelectric point. The seed enzyme has a pl of 5.1, and the root enzyme has a pI of 4.5. The cytoplasmic enzyme from etiolated shoots is slightly acidic with a pI of 5.7 to 6.1 and is found in two separable forms. The chloroplast enzyme (from green sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
26
0

Year Published

1976
1976
1982
1982

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(27 citation statements)
references
References 21 publications
1
26
0
Order By: Relevance
“…The relation of the partially purified regulatory form of the enzyme used in the present investigation to the pure preparations of a form of the enzyme that did not require activation (16,29) remains to be determined.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relation of the partially purified regulatory form of the enzyme used in the present investigation to the pure preparations of a form of the enzyme that did not require activation (16,29) remains to be determined.…”
Section: Methodsmentioning
confidence: 99%
“…Anderson (1) previously observed an enhancement of the NADP-glyceraldehyde-3-P dehydrogenase activity in extracts of etiolated peas when the assay was executed in the presence of DTT. 16 ,ug of Chl or partially purified regulatory enzyme (9 ,ug of protein) was preincubated for 3 min in 0.1 ml of a solution containing 10 umol of Tricine-NaOH buffer (pH 8.4) and, as indicated, I ,umol of DTT and 50 pAg of thioredoxin. After preincubation, the mixture was injected into a 1-cm cuvette of l-ml capacity that, in a final volume of 0.9 ml, contained 2 units of glycerate-3-P phosphokinase and the following (umol): TricineNaOH buffer (pH 8.4), 40; MgSO4, 10; Na-glycerate-3-P, 5 pmol of Tricine NaOH buffer (pH 8.4).…”
Section: Methodsmentioning
confidence: 99%
“…In higher plants, NADPH-specific glyceraldehyde-3-P dehydrogenase (NADP-GPDH) (EC 1.2.1.13) occurs only in photosynthetic tissue (4,11,12,14). Seedlings grown in the dark contain little NADPH-GPDH activity, but the enzyme activity increases markedly if the seedlings are exposed to the light (14,19,20). A comprehensive investigation of the specificity of glyceraldehyde-3-P dehydrogenase was done by Pupillo (24) and Pupillo and Piccari (25) who concluded that in all green plants both the NADand NADP-dependent GPDH activities of chloroplasts are catalyzed by one enzyme which is different from the NAD-linked cytoplasmic enzyme.…”
mentioning
confidence: 99%
“…Schulman and Gibbs (26) were unable to separate the NADP and NAD linked GPDH activities from spinach leaves, and pea shoots. More recently McGowan and Gibbs (20) found that the enzyme purified from seeds, roots, and etiolated and green shoots of pea consisted of tetramers with subunits of 35,000 daltons. Based on isoelectric point and immunodiffusion experiments, they concluded that the primary sequences of amino acids in the chloroplast enzyme and in the cytosol enzyme are different.…”
mentioning
confidence: 99%
“…A cytoplasmic enzyme (EC 1.2.1.12), which absolutely requires NAD' as coenzyme, has been isolated from seeds, roots and etiolated leaves [1,2]. All these cytoplasmic enzymes have very similar properties to the enzymes purified from animal muscle.…”
mentioning
confidence: 99%